Studies on the influence of rotor distance on the efficiency of a coaxial rotor system - Kränzler, M.; Dufhaus, S.; Stumpf, E. (My University, 2018)
Coaxial rotor systems are of special interest on aircraft with electric propulsion. An experimental analysis of the performance of such a system is described in this paper. Two rotors with identical geometry are operated at an equal rotational speed. The presented test bench allows to measure electrical and force data individually for both rotors. Analyses are conducted in the hover case as well as in a case with an axial incidence flow in a wind tunnel for various rotor separation distances. Efficiency of the rotor system is compared to a single rotor. It is shown that the separation distance of the rotors has a strong influence on the upper and lower rotor individually, although the combined performance is approximately independent in the hover case. In the case with an axial incidence flow, overall efficiency of the analyzed rotor system increases for a smaller rotor separation distance.